Improving Storytelling Ability Using Implications of The Read-Aloud Method in Early Childhood - Nur Aini; Meri Hartati; Ichsan Maulana Azhari (JOYCED: Journal of Early Childhood Education, 2023)
Basically, a school for early childhood takes work. Many factors influence this, including the shy factor that makes you afraid to speak or tell stories. If the problem is not resolved immediately, it will be difficult for the child to express his feelings. The Read-Aloud method trains children to be able to retell the contents of fairy tales and stories to increase children's vocabulary. Packaging the Read Aloud method uses the media of illustrated children's story books and fairy tale books that can make young children interested in following them. In this study, the authors used a qualitative descriptive method. Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that the implications of the Read Aloud method can stimulate early childhood development by increasing vocabulary so children's language skills can develop properly. Obstacles in this study were limited by changes in the behavior of research subjects which made researchers increase research time.